2000
DOI: 10.1054/bjoc.1999.1029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modelling of epithelial and stromal interactions in non-malignant and malignant prostates

Abstract: SummaryTo study the effects of stromal epithelial cell interactions on prostate cancer metastasis, we have used primary human prostatic stromal cells derived from malignant and non-malignant tissues and established epithelial cell lines from normal (PNT1a and PNT2-C2) and tumour (PC-3, DU145 and LNCaP) origins. The effects of stromal cells on epithelial cell growth were studied in direct and indirect (using culture inserts) co-culture and by exposure to stromal cell-conditioned medium (assessed by MTT assay). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 21 publications
4
33
1
1
Order By: Relevance
“…This invasive phenotype can be further augmented in the presence of stromal cells as a consequence of their high ECE-1 expression and ET-1 availability to the tumour. The role of stromal involvement during PC progression has been reported elsewhere (Lang et al, 2000), and this is consistent with recent observations that epithelial -stromal interactions are critical determinants of tumour cell behaviour. Ramaswamy et al (2003) compared the geneexpression profiles of metastatic adenocarcinomas with their primary counterparts and found that a considerable proportion of the refined geneexpression signature associated with metastasis was derived from the nonepithelial components of the tumour.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This invasive phenotype can be further augmented in the presence of stromal cells as a consequence of their high ECE-1 expression and ET-1 availability to the tumour. The role of stromal involvement during PC progression has been reported elsewhere (Lang et al, 2000), and this is consistent with recent observations that epithelial -stromal interactions are critical determinants of tumour cell behaviour. Ramaswamy et al (2003) compared the geneexpression profiles of metastatic adenocarcinomas with their primary counterparts and found that a considerable proportion of the refined geneexpression signature associated with metastasis was derived from the nonepithelial components of the tumour.…”
Section: Discussionsupporting
confidence: 91%
“…The invasion assay was performed essentially as described by Lang et al (2000). The following supplements were added, either alone or in combination, to both STO (stromal) cell (bottom well) and epithelial cell (top well) media: NEP (50 mg ml À1 ), thiorphan (1 mM), bradykinin (100 nM), ET-1 (10 nM) and the specific ECE inhibitor ECE-i (100 nM).…”
Section: Invasion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The PC-3 cell line and cells derived from patients with CaP showed colonies and cells which appeared spiky and scattered whilst the PNT2-C2 cell line and cells derived from patients with BPH showed rounded colonies. This confirmed findings previously reported (Lang et al, 2000) which suggests a more motile and invasive nature of PC-3 and CaP derived epithelial cells. Regarding proteolytic enzyme production in BMS co-culture, we found that when cells derived from patients with CaP were grown in BMS co-culture, not only were the epithelial cells strongly stained for MMP-1, the stromal cells around the leading edge of the colony were also strongly positive.…”
Section: Discussionsupporting
confidence: 92%
“…12,13 Many research groups have also shown that a dynamic stromal-epithelial interaction plays a critical role in the progression and metastasis of PCa. [14][15][16][17][18][19][20] Growth factors play a central role in mediating the interactions between epithelial and stromal cells. 21 The stromal-epithelial interaction is also critical for mediating the effects of these molecules on epithelial cells.…”
Section: Introductionmentioning
confidence: 99%